Literasi AI dalam Pemanfaatan Canva pada Siswa Jurusan Desain Komunikasi Visual SMK Muhammadiyah 2 Palembang - Ilsa Palingga Ninditama; Dita Rahmawati; Agung Indriansyah; Aimi Aimi; Sinta Bella Agustina; M Bambang Purwanto (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
This Community Service (PKM) activity aims to improve artificial intelligence (AI) literacy in students majoring in Visual Communication Design (DKV) at SMK Muhammadiyah 2 Palembang through Canva-based training. The development of AI technology has brought about a significant change in the world of graphic design, where features such as Magic Design, Text-to-Image, and Background Remover are now widely used to support the creative process. However, most vocational school students are still passive users, lacking an understanding of the AI principles behind the technology. Through a Project-Based Learning (PjBL) and Active Learning approach with a demo–practice–reflection model, this activity is designed so that students are not only able to use the AI features in Canva, but also understand the work concepts, benefits, and ethics of using them. The activity was conducted over two days, involving 30 DKV class XI students. The evaluation of the results showed a significant increase in the aspects of understanding AI concepts (48%), motivation to learn design (35%), and creativity of works (32%). Students also show an increase in learning independence and digital ethical awareness. These results confirm that AI-based learning through Canva is effective in building AI literacy, creativity, and student readiness to face the technology-based creative industry. This activity is recommended to be expanded to teachers and other departments to strengthen digital literacy in the vocational education environment.